Strategies to Genetically Modulate Dendritic Cells to Potentiate Anti-Tumor Responses in Hematologic Malignancies - Cornel, Annelisa M.; van Til, Niek P.; Boelens, Jaap Jan; Nierkens, Stefan (Frontiers in Immunology, 2018)
Dendritic cell (DC) vaccination has been investigated as a potential strategy to target hematologic malignancies, whilst generating sustained immunological responses to control potential future relapse. Nonetheless, few clinical trials have shown robust long-term efficacy. It has been suggested that a combination of surmountable shortcomings, such as selection of utilised DC subsets, DC loading and maturation strategies, as well as tumor-induced immunosuppression may be targeted to maximize anti-tumor responses of DC vaccines. Generation of DC from CD34+ hematopoietic stem and progenitor cells (HSPC) may provide potential in patients undergoing allogeneic HSPC transplantations for hematologic malignancies. CD34+ HSP from the graft can be genetically modified to optimize antigen presentation and to provide sufficient T cell stimulatory signals. We here describe beneficial (gene)- modifications that can be implemented in various processes in T cell activation by DC, among which major histocompatibility complex (MHC) class I and MHC class II presentation, DC maturation and migration, cross-presentation, co-stimulation, and immunosuppression to improve antitumor responses.